2019
DOI: 10.1016/j.bjae.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia for ambulatory surgery

Abstract: Explain the historical context of spinal anaesthesia in the ambulatory setting. Describe the ideal characteristics of an ambulatory spinal anaesthetic. Recognise the central role of prilocaine and 2chloroprocaine in the ambulatory setting. Select the right drug for the right patient and the right procedure. Ambulatory surgery places high demands on anaesthetic technique. In this setting, rapid onset and offset of anaesthesia, rapid recovery of protective reflexes, mobility and micturition, and good control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…Several studies the last past years have shown its efficacy when applied for spinal anesthesia and have determined the appropriate doses for various ambulatory surgery procedures lasting up to 90 min [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies the last past years have shown its efficacy when applied for spinal anesthesia and have determined the appropriate doses for various ambulatory surgery procedures lasting up to 90 min [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years, goal-directed fluid therapy (GDT) has been the gold standard of treatment for cardiovascular optimisation. Randomised control trials investigating GDT report not only improvements in morbidity and mortality but also reduced length of intensive care stay and hospital admission (Jin et al 2018, Rollins & Lobo 2016).…”
Section: Intraoperative Carementioning
confidence: 99%
“…Delivery of warmed fluids throughout the perioperative period by practitioners is essential to prevent hypothermia. Perioperative hypothermia is associated with a range of complications; increased intraoperative blood loss, prolonged recovery with increased duration of inpatient stay, impaired wound healing and cardiovascular complications (Frank et al 1997, Lenhardt et al 1997, Marik & Lemson 2014, Rollins & Lobo 2016). One litre of room temperature crystalloid fluid decreases core temperature by 0.25°C.…”
Section: Intraoperative Carementioning
confidence: 99%
“…Several studies the last past years have shown its efficacy when applied for spinal anesthesia and have determined the appropriate doses for various ambulatory surgery procedures lasting up to 90 minutes. [14][15][16] First introduced for intrathecal use in 1965, 17 the former presentation of prilocaine was assessed in obstetrics for vaginal or cesarean delivery under continuous epidural anesthesia in 1968. 18,19 Good quality of anesthesia was reported with 1%-2% formulations with no clinically relevant blood accumulation of prilocaine, although considerable doses had been administered via the continuous epidural mode.…”
Section: Introductionmentioning
confidence: 99%